Strategi Mahasiswa Dalam Memerangi Politik Uang Sebabkan Kecurangan Pemilu - Ririn Deswita Putri; Nabila Nabila; Renita Br Tompul; Sonia Trifosa Siahaan (Jurnal Relasi Publik, 2024)
General elections are an important part of implementing election strategies to increase public participation by implementing cooperation in communication effectiveness to prevent violations. Student problematic efforts have become a major milestone in voicing aspirations to the government so that both parties prioritize wise character in choosing quality political institutions. Student indicators in carrying out their role are conducting political campaigns that are free of money politics through digital media by disseminating through podcasts, posters distributed through social media to attract audience attention and through other digital media. Public awareness to strengthen the selection of institutions in accordance with one's own decision in order to understand the concept of wise voter participation.